THE EFFECTS OF 8-WEEK CORE STABILIZATION EXERCISES FOR FUNCTIONAL STATE IN HIGH-LEVEL ATHLETES - Aleknavičiūtė-Ablonskė, Vaida; Bubelis, Justinas (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The purpose of this study was to compare clinical results for functional state in high - level athletes before and after 8 - week core stabilization exercise program. After analyzing the publications of many foreign authors, it can be stated that the exercises of core stabilization applied in conjunction with regular training have a positive effect for abdominal and back muscle static strength endurance, posture, neuromuscular control